Effect of the Rebozo Technique on Fetal Head Descent In Cilandak District, South Jakarta, Indonesia - HARIS, VERA SUZANA DEWI (Universitas Aisyah Pringsewu, 2024)
The Rebozo technique can facilitate the descent of the fetal head and cervical dilation by flexing and relaxing the pelvic floor muscles, allowing the fetal head to enter and move down the birth canal. This study aimed to analyze the differences in fetal head descent among pregnant women who received the Rebozo technique and its overall effect on fetal head descent at the Velia Medika Clinic, Cilandak, South Jakarta, in 2023.This quasi-experimental study utilized a pretest-posttest control group design. The research subjects were third-trimester pregnant women at the Velia Medika Clinic. Data were analyzed using paired and independent sample t-tests. The study found that pregnant women in both the intervention and control groups generally had higher education levels, with 78.8% in the intervention group and 72.7% in the control group having at least a high school education. Additionally, the majority of participants were not employed, with 55.5% in the intervention group and 57.6% in the control group.The results indicated that the Rebozo technique significantly accelerates the descent of the fetal head during pregnancy. The independent t-test showed a value of ? = 0.00 ( 0.05), confirming a statistically significant relationship between the Rebozo technique and fetal head descent in third-trimester pregnant women.In conclusion, there are significant differences in fetal head descent between pregnant women who received the Rebozo technique and those who did not. Health workers, particularly midwives, should consider incorporating the Rebozo technique